2000
DOI: 10.1038/35041072
|View full text |Cite
|
Sign up to set email alerts
|

Function of microtubules in intercellular transport of plant virus RNA

Abstract: Cell-to-cell progression of tobacco mosaic virus (TMV) infection in plants depends on virus-encoded movement protein (MP). Here we show that a conserved sequence motif in tobamovirus MPs shares similarity with a region in tubulins that is proposed to mediate lateral contacts between microtubule protofilaments. Point mutations in this motif confer temperature sensitivity to microtubule association and viral-RNA intercellular-transport functions of the protein, indicating that MP-interacting microtubules are fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
173
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(193 citation statements)
references
References 47 publications
15
173
0
5
Order By: Relevance
“…We cannot exclude the possibility that ABD2:GFP binding to actin filaments interferes with MP:RFP binding. However, since other studies have demonstrated that the filaments to which MP binds in plant and mammalian cells are microtubules (Heinlein et al, 1995(Heinlein et al, , 1998Boyko et al, 2000aBoyko et al, , 2000bAshby et al, 2006;Ferralli et al, 2006), this possibility appears unlikely. Our observation is consistent with the finding that MP does not bind to actin filaments in mammalian cells (Ferralli et al, 2006), and actin is highly conserved between plants and mammals.…”
Section: Mp Does Not Align To Actin Filamentsmentioning
confidence: 84%
“…We cannot exclude the possibility that ABD2:GFP binding to actin filaments interferes with MP:RFP binding. However, since other studies have demonstrated that the filaments to which MP binds in plant and mammalian cells are microtubules (Heinlein et al, 1995(Heinlein et al, , 1998Boyko et al, 2000aBoyko et al, , 2000bAshby et al, 2006;Ferralli et al, 2006), this possibility appears unlikely. Our observation is consistent with the finding that MP does not bind to actin filaments in mammalian cells (Ferralli et al, 2006), and actin is highly conserved between plants and mammals.…”
Section: Mp Does Not Align To Actin Filamentsmentioning
confidence: 84%
“…For some viruses, e.g. TMV, the MP interacts with plasmodesmata, increasing their size exclusion limit, and possesses non-specific RNA-binding activity that enables it to form a transportable complex with viral RNA (Wolf et al, 1989;Atkins et al, 1991;Citovsky & Zambryski, 1991 and to microtubules (Boyko et al, 2000). Although TMV CP is essential for long-distance movement, it is not required for cell-to-cell movement (see review by Carrington et al, 1996).…”
Section: Cell-to-cell Movementmentioning
confidence: 99%
“…To date, MP has been shown to bind TMV RNA (Citovsky et al, 1990(Citovsky et al, , 1992, associate with the cytoskeleton (Heinlein et al, 1995;McLean et al, 1995;Boyko et al, 2000) and endoplasmic reticulum (ER; Heinlein et al, 1998;Reichel and Beachy, 1999), target to plasmodesmata within plant cell walls (Tomenius et al, 1987;Ding et al, 1992a), increase plasmodesmal permeability (Wolf et al, 1989;Waigmann et al, 1994), and undergo negative regulation by phosphorylation (Citovsky et al, 1993;Waigmann et al, 2000;Trutnyeva et al, 2005). To perform many of these functions, TMV MP most likely cooperates with different cellular factors, some of which, such as cell wall pectin methylesterases (PME; Dorokhov et al, 1999;Chen et al, 2000), microtubules (MTs) and actin filaments (Heinlein et al, 1995;McLean et al, 1995;Boyko et al, 2000), and a RIO protein kinase (Yoshioka et al, 2004), are known, while others remain to be discovered. It would be especially interesting to determine whether cellular proteins exist that not only recognize TMV MP but also coreside with it within plasmodesmata.…”
mentioning
confidence: 99%